Anxiety Disorders From Childhood to Adulthood - Kocabaşoğlu, Neşe; Hülya Bingöl Çağlayan, R. (IntechOpen, 2019)
In this book, we focus on children with anxiety disorders and the children whose parents were diagnosed with anxiety disorders in their lifetime. The aim is to investigate the different types of anxiety disorders with different underlying mechanisms. The developmental perspective will support a better understanding of the development of anxiety disorders and transition from childhood to adulthood. We believe this book will appeal to a wide audience of practicing psychiatrists, psychologists, psychiatric nurses, social workers and mental health professionals. It is our hope that many will find this book useful for training mental health professionals to give them the newest developmental point of view about prototype anxiety disorders. We dedicate this book to our lovely families, patients, and their families.